2017
DOI: 10.1016/j.atherosclerosis.2017.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of fish and vascular risk factors: A systematic review and meta-analysis of intervention studies

Abstract: This study showed that there is evidence indicating that consuming oily fish led to significant improvements in two important biomarkers of cardiovascular risk, such as triglycerides and HDL levels. These results strongly support the important role for oily fish as part of a healthy diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 41 publications
2
48
0
2
Order By: Relevance
“…Additionally, neither high nor low fat dairy products seem to affect cardiovascular risk factors ( 129 ). Consumption of fatty fish resulted in significant improvements in TG and HDL cholesterol, whereas no effects were observed for TC, LDL cholesterol, DBP, SBP, FG, and CRP ( 130 ). Regarding red meat intake, a systematic review suggested that consumption of ≥0.5 servings/d of total red meat has no detrimental effect on blood lipids or blood pressure compared with lower red meat intakes ( 131 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, neither high nor low fat dairy products seem to affect cardiovascular risk factors ( 129 ). Consumption of fatty fish resulted in significant improvements in TG and HDL cholesterol, whereas no effects were observed for TC, LDL cholesterol, DBP, SBP, FG, and CRP ( 130 ). Regarding red meat intake, a systematic review suggested that consumption of ≥0.5 servings/d of total red meat has no detrimental effect on blood lipids or blood pressure compared with lower red meat intakes ( 131 ).…”
Section: Discussionmentioning
confidence: 99%
“…KEYWORDS confocal laser scanning microscopy, fat content, growth morphology, Listeria monocytogenes, microcolony size I n recent years, global fish product consumption has increased significantly (1)(2)(3). Fish products are known to be beneficial for human health, being an important source of high-quality proteins, vitamins, minerals, and omega-3 fatty acids (4)(5)(6). However, contamination with foodborne pathogens is common in fish products, as illustrated by the percentage of foodborne outbreaks caused by products of this food category, e.g., 5.4% in 2016 (7).…”
mentioning
confidence: 99%
“…Moreover, several studies have found either that meat intake has no association with mortality/morbidity, or that meat restriction is association with various negative health outcomes (e.g., Key et al, 2009;Burkert et al, 2014;Kwok et al, 2014;Lippi et al, 2015;Hur et al, 2018;Iguacel et al, 2018;Yen et al, 2018). As another example of conflicting information, the epidemiological association pointing to a potential role of the meat nutrient L-carnitine in atherosclerosis via trimethylamine N-oxide (TMAO) formation (Koeth et al, 2013), is contradicted by intervention studies (Samulak et al, 2019) and epidemiological data showing that fish intake, being by orders of magnitude the largest supplier of TMAO (Zhang et al, 1999), improves triglycerides and HDL levels (Alhassan et al, 2017).…”
Section: A Scientific Assessment Should Not Overlook Conflicting Datamentioning
confidence: 99%